Climate Risk Country Profile : Indonesia - World Bank Group; Asian Development Bank (World Bank, Washington, DC and Asian Development Bank, Manila, 2021)
The Republic of Indonesia, herein Indonesia, is the world’s largest archipelagic state, consisting of more than 17,500 islands with over 81,000 kilometres (km) of coastline, a population of 270.6 million as of 2019 and the largest economy in Southeast Asia. Indonesia is highly vulnerable to climate change impacts, including extreme events such as floods and droughts, and long-term changes from sea level rise, shifts in rainfall patterns, and increasing temperature. This document aims to succinctly summarize the climate risks faced by Indonesia. This includes rapid onset and long- term changes in key climate parameters, as well as impacts of these changes on communities, livelihoods, and economies, many of which are already underway. This is a high-level synthesis of existing research and analyses, focusing on the geographic domain of Indonesia, therefore potentially excluding some international influences and localized impacts. The core data presented is sourced from the database sitting behind the World Bank Group’s (WBG) climate change knowledge portal (CCKP), incorporating climate projections from the Coupled Model Inter-comparison Project Phase 5 (CMIP5). This document is primarily meant for WBG and Asian Development Bank (ADB) staff to inform their climate actions. The document also aims and to direct the reader to many useful sources of secondary data and research.